The role of early post radiation MRI scans in children with diffuse intrinsic pontine glioma (DIPG) - Ko, Christine (Int J Radiat Oncol Biol Phys, 2012)
PURPOSE: To determine optimal timing of assessing post-radiation radiographic response on MRI scans in pediatric patients with diffuse intrinsic pontine glioma (DIPG). METHODS AND MATERIALS: Patients were treated on a prospective study at the National Cancer Institute (Protocol #06-C-0219) evaluating the effects of radiation therapy. Standard RT was administered in standard fractionation over six weeks. Post-radiation MRI scans were performed at 2 and 6–8 weeks. RESULTS: 11 patients with DIPG were evaluated. Median age was 6 yrs (range: 4–13 years). Patients were treated with EBRT to 55.8 Gy (n=10) or 54 Gy (n=1) with a GTV to PTV expansion of 1.8–2.0 cm. All patients received prescribed dose and underwent post-treatment MRIs at 2 and 6–8 weeks. Pretreatment imaging revealed compression of fourth ventricle (n=11); basilar artery encasement (n=9); tumor extension outside the pons (n=11); tumor hemorrhage (n=2). At the 2 week scan, basilar artery encasement improved in 7/9 patients, extent of tumor was reduced in 5/11 patients. Fourth ventricle compression improved in 6/11 patients but worsened in 3/11 patients. Presumed necrosis was observed in 5/11 patients at 2 weeks; 1 additional patient at 6–8 weeks. There was no significant difference in mean AP and transverse diameters of tumor between the 2 and 6–8 week time points. 6/11 patients had increasing ventricular size with no evidence of obstruction. CONCLUSIONS: There is no significant difference in tumor size of DIPG patients who have received standard RT when measured at 2 weeks versus 6–8 weeks post RT. The majority of patients had the largest change in tumor size at the 2 week scan post-RT with evolving changes documented on the 6–8 week scan. 6/11 patients had progressive ventriculomegaly without obstruction, suggestive of communicating hydrocephalus. To the best of our knowledge, this is the first documentation of this phenomenon in this cohort of patients.